Davunetide: Peptide Therapeutic in Neurological Disorders - Magen, Iddo; Gozes, Illana (Current Medicinal Chemistry, 2014)
This review focuses on the therapeutic effects and mechanisms of action of NAP (davunetide), an eight amino acid snippet derived from activity-dependent neuroprotective protein (ADNP) which was discovered in the laboratory of Prof. Illana Gozes. The effects of NAP and its related peptides in models of neurodegenerative diseases and other neurological disorders will be described here in details. Possible mechanisms of NAP actions include anti-inflammatory effect, antioxidant activity, inhibition of protein aggregation and interaction with microtubules. In line with the fact that all of these features are characteristic to most neurological/neurodegenerative disorders, NAP was found to have beneficial effects on the behavioral manifestations associated with these disorders.
Keywords: neurodegenerative diseases